2017
DOI: 10.21894/jopr.2017.2902.03
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Vector Containing Hygromycin (Hpt) Gene Driven by Double 35s (2xcamv35s) Promoter for Oil Palm Transformation

Abstract: Transformation vector construction is one of the important disciplines for plant genetic transformation studies. A series of vector consisting of hygromycin phosphotransferase (hpt) gene as the selective marker and green fluorescent protein (GFP) as the visual reporter gene, under the control of double cauliflower mosaic virus 35S (2XCaMV35S) promoter has been engineered for transformation into oil palm cells. These genes were cloned into different types of cloning and expression vectors. The cloning was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In order to investigate the potential use of hpt gene for selection of hygromycin resistant transgenic plants, two vectors namely pBIHA-X (10 810 bp) in pCAMBIA0380 backbone, which was successfully constructed in this study and pBIHA1 (14 194 bp) in pBINPLUS backbone which was previously reported (Bahariah et al, 2017) were evaluated in this study (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to investigate the potential use of hpt gene for selection of hygromycin resistant transgenic plants, two vectors namely pBIHA-X (10 810 bp) in pCAMBIA0380 backbone, which was successfully constructed in this study and pBIHA1 (14 194 bp) in pBINPLUS backbone which was previously reported (Bahariah et al, 2017) were evaluated in this study (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The pBIHA-X (p2X35SHPTGFP-0380) plasmid was constructed to contain the hpt selectable marker and gfp reporter genes driven by 2XCaMV35S in . The construction was carried out by employing two intermediate plasmids, p2X35STEVHPT-GII (5.5 kb) and p2X35STEVGFP-GII (5.2 kb), created in the earlier study (Bahariah et al, 2017). The p2X35STEVHPT-GII fragment was ligated to the HindIII and EcoRI sites of pCAMBIA0380 to form 8.9 kb of p2X35STEVHPT-0380.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CRISPR/Cas9 constructs were introduced into oil palm calli using biolistic and Agrobacterium -mediated transformation, while PEG-mediated transfection was used to introduce the constructs into oil palm protoplasts according to the established protocol [ 6 , 28 30 ]. The calli were then selected for regeneration on 4 mg liter −1 of hygromycin selective agent under 16/8 h light conditions at 28 °C.…”
Section: Methodsmentioning
confidence: 99%